Reposition Malaysian’s Social Neuroscience Life Cycle Paradigm to Resolve the Midlife Mystic - Boey, Loh Hock (Integrated Journal for Research in Arts and Humanities, 2022)
This investigation examines, via phenomenological qualitative analysis, on the agony of midlife progression shocked many underwent, when march in to the beclouded forty unprepared due to society knowledge deficiency on the existent of midlife phase. Thus, the key research objective is to reposition the subject of life cycle paradigm by setting a new psychosocial parameter for each life phase by defining it from the social neuroscience perspective, so that to devise a new model of social neuroscience life cycle paradigm for Malaysian. A qualitative inquiry on the individual’s lived phenomenological experiences within the social structure is done by face to face interview, then snow ball to people around them by survey form. A total of N=221 Malaysian participated voluntarily by answering three fundamental questions to elicit their personal life experience on the social neuroscience dimensions. The answer is scripted for thematic analysis and tested by SPSS. 68% of data collected from people originated from other states, thus the statistic could then be considered as Malaysia’s. Three major finding resulted. Firstly, there are four episodes life cycle of life span on one’s whole life, yet only 15.4% of Malaysian acknowledge the existent of midlife episode as a process and majority (76%) define life process as a simple three episode process. Secondly, the accretion of 11 social neuroscience dimensions in one’s life course, and reveals a mystical existent of social assumed illusion on midlife as steady stage outwardly with specialised skills, which has wrapped up their inward neuroscience struggle of vulnerability that need emotional regulation of this latent effect. Thirdly, when the two finding are mixed, a new look of Malaysian social neuroscience life cycle paradigm named as “The 28,000 days of four episodes social neuroscience life cycle” is born and presenting a new era for whole life transition analysis. The two immediate contribution of this study produces a new era concept that has walked Malaysian from knowledge darkness of life episodes by elevating life cycle paradigm into a new level on social neuroscience aspects, and, invented a crisis predictability to curb the hidden explosive crisis dynamic, though not able to eliminate it during midlife. Process from here, next research should be on a bigger quantitative scale research dynamic of psychosocial factors which trigger specifically hidden midlife crisis knowledge deficiency.